Chemical engineering design - Sinnott, Raymond K., ....- (Amsterdam : Elsevier, 2005)
Chemical Engineering Design is one of the best-known and widely adopted texts available for students of chemical engineering. It deals with the application of chemical engineering principles to the design of chemical processes and equipment. Revised throughout, the fourth edition covers the latest aspects of process design, operations, safety, loss prevention and equipment selection, among others. Comprehensive in coverage, exhaustive in detail, it is supported by extensive problems and a separate solutions manual for adopting tutors and lecturers. In addition the book is widely used by professionals as a day-to-day reference.
Previous editions have title: Chemical engineering.
Includes bibliographical references and indexes.
Keywords: Chemical engineering; Chemische industrie; Ontwerpen; Procesontwerp